Communicating in English : talk, text, technology - Allington, Daniel; Mayor, Barbara M., 1949- (Milton Park, Abingdon, Oxon : Routledge, 2012)
'Communicating in English: Talk, Text, Technology looks at how people use spoken and written English to communicate in their everyday lives. Exploring the complex relationship between communication, technology and the English language, this book offers the reader practical insights into the analysis of speech and writing. A wide range of examples is provided, ranging from text messages and domestic quarrels to the works of Shakespeare and the words of Martin Luther King. This book takes a fresh look at established topics such as rhetoric, language acquisition, and professional communication, as well as covering exciting new fields such as everyday creativity, digital media, and the history of the book. Key theoretical concepts are introduced in an accessible manner, and the reader is given an in-depth understanding of English-language communication in its social and historical contexts.'--Publisher's website.
Includes bibliographical references (p. 349-363) and index.
Keywords: English language -- Textbooks for foreign speakers; English language -- Spoken English; Text messages (Cell phone systems); Communication